Factors structuring estuarine and coastal fish communities across Japan using environmental DNA metabarcoding - Manabu Kume (Elsevier, 2021)
Estuarine and coastal ecosystems are important habitats for many fish species. Large-scale patterns of estuarine and coastal fish communities can be affected by geographical factors, such as water temperature and latitude, that limit or allow fish dispersal, and/or by environmental factors that select locally adapted species. Furthermore, increased human activity has also altered fish diversity by modifying estuarine/coastal environments. Here, we used environmental DNA metabarcoding to study a large-scale pattern of estuarine/coastal fish communities across 25 watersheds in the Japanese Archipelago, and we assessed the effects of geographical, environmental, and anthropogenic factors in structuring these communities. Of the 290 fish species detected, 47 species were red-listed by the Japanese Ministry of Environment, and nine were alien. Non-metric multidimensional scaling showed that latitude and water temperature affected both river-mouth and coastal-sea fish communities. Although other anthropogenic factors did not affect these communities, bank artificialisation rates influenced both. The relationship between each fish community and ocean currents was weak. The number of red-listed fish affected both fish community structures, whereas that of alien species did not. The numbers of red-listed fish in coastal points and of all fish species were negatively influenced to the human population density. These findings provide useful information that may be used to conserve estuarine and coastal ecosystems.